Exploring Marketing Communication Strategies and Islamic Ethics in TikTok Live Streaming for Social Commerce - Abbrar, M Chairil; Sumarlan, Iman (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study explores marketing communication strategies and the application of Islamic ethics in TikTok live streaming within social commerce. As live streaming becomes a prominent promotional tool, understanding its ethical implications is essential, especially for Muslim entrepreneurs. This qualitative research employed semi-structured interviews with selected TikTok influencers and micro-entrepreneurs actively engaged in live selling. The findings reveal that effective marketing strategies on TikTok include real-time audience engagement, influencer credibility, scarcity-based promotions, and informal entertainment styles to build emotional connections. However, several practices conflict with Islamic ethical principles, particularly regarding truthfulness (ṣidq), trustworthiness (amānah), and respectful conduct (adab). Exaggerated product claims and misleading demonstrations were observed, potentially violating Islamic business ethics. The study concludes that while TikTok live streaming offers strategic advantages for social commerce, ethical compliance remains a challenge. It recommends increasing digital ethical literacy and developing Islamic marketing guidelines for practitioners. These findings contribute to a deeper understanding of how contemporary digital marketing can align with religious values in the evolving landscape of e-commerce.